PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SMARTPHONE MENGGUNAKAN APLIKASI CANVA TERHADAP MINAT DAN HASIL BELAJAR SISWA - Lestari, Dwi; Kantun, Sri; Herlindawati, Dwi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
One aspect that teachers in learning activities must consider is the use of learningmedia. Appropriate learning media will impact students' learning interests so thatthey can easily capture and digest the material the teacher explains. The higher theinterest of students in learning activities, the results obtained by students will bemore optimal. This study aims to determine the significant influence of smartphonebased interactive learning media using Canva applications on learning interestsand student learning outcomes. The research method used is quasi-experimentalwith a non-equivalent control group design and two meetings. This study uses fiveresearch instruments: questionnaires, tests, interviews, observations, anddocuments. Data analyst techniques used in the study include the hypothesis test, ttest, and test path analysis. The results showed that there is a significant effect ofsmartphone-based interactive learning media using the Canva application onlearning interest, obtaining a value of 0.000<0.05; student learning interest onstudent learning outcomes obtained a value of 0.021< 0.05; and the effect ofsmartphone-based interactive learning media using the Canva application onlearning outcomes through student learning interest obtained a value of 0.031<0.05.